A solution to the frequency regulation problem in the Luzon power grid - Lamdagan, Ray Alfonso G. (1994)
The Luzon power grid is encountering a frequency regulation problem in which a solution is being sought. Dynamic models of the power system, the speed governing system and the different types of prime movers are set up as block diagrams. A set of first order linear differential equations are formed based on these block diagrams and are solved using numerical integration methods. The dynamic response of the Luzon grid with the present method of frequecy control are determined using these models and results show the present method could not prevent Automatic Load Dropping (ALD) for a generation loss of more than 82 MW and could not maintain the frequency deviation within the +/- 0.2 Hz limit. The new method of load-frequency control for the Luzon Grid is basically to operate the two existing automatic load-frequency control systems. These two systems, which have different purposes, are the speed governor, which comprises the primary control system, and the automatic generation control (AGC) which is the secondary or supplementary control system. Fast frequency decay caused by generator tripping is arrested by these speed governors. But the action of these speed governors alone could not restore the frequency error to zero. It is the supplementary control that slowly brings the frequency back to 60 Hz. The steady state frequency error is smaller if the system static gain is high (more units are operating on free governor). Automatic Load Dropping (ALD) could be prevented if the static gain is equal to the size of the generation loss divided by 0.4 and if there is an effective spinning reserve or frequency regulation reserve equal to the generation loss. These frequency regulation reserves can be brought into the system quickly through governor action. Computer simulations show that during period of low static gain and low frequency regulation reserve, ALD could be prevented by automatic shutdown of the Kalayaan pump-storage plant. In this paper, guidelines for setting AGC unit and system parameters are formulated and tested on several simulation runs to satisfy the following objectives 1.) no control overshoot 2.) minimize unnecessary control and chasing of high frequency random load changes. 3.) better tracking of economic dispatch targets 4.) smooth and lesser frequency excursions. Simulation results show that proper setting of AGC parameters will minimize unnecessary control of units and therefore result in less wear and tear, and that frequency control with economic dispatching of thermal plants is feasible. Actual results show that the system performance, based on the NERC criterion, of the new method of frequency control is superior to that of the old method.